The Getting To Know The Various Schools Of Philosophical Thinking Methods in The Implementation Of Management - Ivan Widjaja; Adi Hermawansyah; Agung Winarno (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This article discusses various philosophical thinking methods that have significantly impacted the implementation of management science. Philosophical schools such as rationalism, empiricism, skepticism, idealism, and pragmatism offer unique perspectives on understanding reality and knowledge and how these can be applied in management practice. This research aims to identify philosophical paradigms that can help mitigate risks in management and comprehensively apply the fundamentals of social science. Through a literature review approach, the results show that philosophical thinking methods enhance managerial flexibility and open space for systematic thinking in decision-making.